Dalla robotica alla pandemia. Un itinerario sulla consuetudine attraverso le law and humanities - Campo, Alessandro (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
Science fiction literature symbolically orients the European legislation. One wonders what kind of art might arise in human-robot relations, once we think from the point of view of the legal custom and no longer from the one of the law. Thinking about the lockdown as a scenario in which we have changed our relationship with technology, it’s possible to imagine something about the law and humanities of the future.